2018
DOI: 10.4995/wrs.2018.8781
|View full text |Cite
|
Sign up to set email alerts
|

White lupin bran and its effects on the growth performance, carcass characteristics and digestibility of nutrients in fattening rabbits

Abstract: The purpose of the present study was to evaluate the effects of including white lupin bran (WLB) in a fattening rabbit diet on growth, carcass traits and nutrient digestibility. The C diet (control) based on alfalfa meal, whereas the WLB 5 and WLB 15 diets were based on white lupin bran (crude protein 152 g/kg, neutral detergent fibre 524 g/kg as-fed basis). The WLB 5 diet contained 50 g of white lupin bran/kg instead of 50 g of alfalfa meal/kg, whereas the WLB 15 diet contained 150 g of white lupin bran/kg, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…It is well known that feed costs could be minimized by using cheaper and non-traditional feed ingredients. Furthermore, possible effects on animal growth performance must also be evaluated (De Blas et al, 2018 andUhlířová et al, 2018). Effective utilization of available feed resources is the key to economical livestock rearing (Beigh et al, 2017 andMudgal et al, 2018).…”
Section: Economical Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that feed costs could be minimized by using cheaper and non-traditional feed ingredients. Furthermore, possible effects on animal growth performance must also be evaluated (De Blas et al, 2018 andUhlířová et al, 2018). Effective utilization of available feed resources is the key to economical livestock rearing (Beigh et al, 2017 andMudgal et al, 2018).…”
Section: Economical Efficiencymentioning
confidence: 99%
“…The rising prices of feed ingredients frequently used in animal feeding has led to the evaluation of alternative and less costly ingredients, as feeds which can be accounted for up to 70% of the total costs of rabbit production (Gidenne et al, 2017). Therefore, it could be argued that feed costs could be minimized by using cheaper, non-traditional feed ingredients (de Blas et al, 2018 andUhlířová et al, 2018). The chickpea (Cicer arietinum L.) and lentil (Lens culinaris L.) are cultivated for their edible seeds, they are the major legumes in the Mediterranean Basin.…”
Section: Introductionmentioning
confidence: 99%
“…AOAC (1990) procedures were used to determine dry matter, (DM; 934.01), organic matter (OM; 942.05), crude protein (CP; 954.01), crude fibre (962.09) and ether extract (920.39). Neutral detergent fibre (NDF), acid detergent fibre (ADF) and lignin fractions were obtained by the detergent methodologies without the use of sodium sulphite and expressed exclusive of ash (Robertson and Van Soest, 1981;Van Soest et al, 1991). The acid detergent-insoluble nitrogen (ADIN) was determined according to Goering and Van Soest (1990).…”
Section: Chemical Analysismentioning
confidence: 99%
“…However, the rising prices of ingredients frequently used in animal feeding has led to the evaluation of alternative and less costly ingredients, as feed can account for up to 70% of the total costs of rabbit production (Gidenne et al, 2017). Although it could be argued that feed costs could be minimised by using cheaper, nontraditional feed ingredients, the inclusion of these feed resources is limited, as most of the times data on their nutritive value are scarce and highly variable (Lima et al, 2017;de Blas et al, 2018;Uhlířová et al, 2018). Furthermore, possible effects on animal growth performance must also be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…As far as the dietary utilization of byproducts in rabbits is concerned, a list of different products from agro-industrial processes may be drafted. It has been reported that coproducts, such as wheat bran [7], sugar beet pulp [8], sunflower hulls [9], soybean hulls [10], lupine hulls [11], lupine bran [12], soybean meal and sunflower meal [13], rapeseed meal [14], distillers dried grains with solubles [15], dried brewers' grains [16], coproducts from olive cake [17], citrus coproducts [18], and defatted grape seed meal [19], can be suitable diet components for rabbits.…”
Section: Introductionmentioning
confidence: 99%